Noise Mitigation and Related Factors of High Speed Railways - Watson, Inara; Ali, Amer; Bayyati, Ali (European Journal of Sustainable Development, 2018)
The continuing rise of population and globalisation have a large impact on the transport system. Railway transport, particularly High-Speed Railways (HSR) offers many advantages compared with other modes of transportation. HSR can reduce the amount of pollution from transport and ease congestion on roads and at airports. High speed railways may mean more noise and vibration which reduce the quality of life, disturb sleep and negatively affect health in addition to other impacts on the wild life and nature in general. Therefore, it is very important for the development of HSR systems to consider effective measures to reduce the level of noise and vibration among its most important goals. This paper reports on a research that takes the form of an investigation and critical evaluation of the key existing factors that contribute to noise emissions from HSR and discusses possible ways to reduce them. A comparison of different influential factors and mitigation measures concerning a selected HSR systems will be reported. From the evidence that has been gathered from different sources and related critical evaluations, conclusions can be made to show that in some cases the increases in speed would not only be a threat to the environmental sustainability but also affect the economical sustainability of HSR systems. Most of the findings are based on research by the authors and data gathered from relevant sources including in depth research concerning HSR systems in selected countries, available railway statistics and relevant European and Institutional Publications. The expected outcomes of this research will contribute to the development and advances of more sustainable HSR systems that can meet the growing demand for travel due to the continuing growth in world population and globalization. Keywords: High-speed rail, noise mitigation, environment, sustainability.